Practitioners' Views on Five-Year Educational Requirements for CPAs. - Arnold, Donald F.; Geiselhart, Thomas J. (The Accounting Review, 1984)
ABSTRACT: With the expanding body of knowledge required of CPAs, there has been significant support in recent years for expanding the educational requirement for accountants from four to five years. This paper reports the results of a questionnaire distributed to practicing CPAs regarding their opinions on the effect and impact of a required fifth year of accounting education. Issues covered include the perceived effects of additional education on the CPA examination passage rate, on the value of the employee to the firm and the profession, and on the supply of accountants. Preferences on the timing and content of five-year programs and the problems of reciprocity were also examined.